For a New Kind of History: A Reconnaissance of 100 Years of Canadian Socialism - McKay, Ian (Labour/Le Travailleur, 2000)
Abstract The turn of the millennium also marks the centenary of Canadian socialism, dated from 1901 (the first free-standing country-wide organization) or 1905 (the formation of the first electorally successful socialist party). By probing the logic and rhetoric of key texts from the Canadian socialist movement, we can discern four distinct formations — evolutionary science, revolutionary praxis, national state management, and revolutionary humanism and national liberation — in a history marked throughout by a hegemonic liberal order. These strategies are worth careful, sympathetic, and critical study as socialist movements regroup in the 21st century.